Primary lysosomal dysfunction causes cargo-specific deficits of axonal transport leading to Alzheimer-like neuritic dystrophy - Sooyeon Lee; Yutaka Satō; Ralph A. Nixon (2011)
Abnormally swollen regions of axons and dendrites (neurites) filled mainly with autophagy-related organelles represent the highly characteristic and widespread form of "neuritic dystrophy" in Alzheimer disease (AD), which implies dysfunction of autophagy and axonal transport. In this punctum, we discuss our recent findings that autophagic/lysosomal degradation is critical to proper axonal transport of autophagic vacuoles (AVs) and lysosomes. We showed that lysosomal protease inhibition induces defective axonal transport of specific cargoes, causing these cargoes to accumulate in axonal swellings that biochemically and morphologically resemble the dystrophic neurites in AD. Our findings suggest that a cargo-specific failure of axonal transport promotes neuritic dystrophy in AD, which involves a mechanism distinct from the global axonal transport deficits seen in some other neurodegenerative diseases.